Identification of a metabolic brain network characterizing essential tremor - Solange Volnov; Hamzah Baagil; Oliver Winz; Hans-Juergen Kaiser; Sanne Katherina Meles; Joerg Bernhard Schulz; Kathrin Reetz; Felix Manuel Mottaghy; Florian Holtbernd (Scientific Reports)
Abstract The neuronal correlate of tremor genesis and cognitive function in essential tremor (ET) and its modulation by deep brain stimulation (DBS) are poorly understood. To explore the underlying metabolic topography of motor and cognitive symptoms, sixteen ET patients (age 63.6 ± 49.1 years) and 18 healthy controls (HC) (61.1 ± 6.3 years) underwent tremor and cognitive assessments and18F-fluorodeoxyglucose PET of the brain. Multivariate spatial covariance analysis was applied for identifying ET related metabolic brain networks. For network validation and to explore DBS effects, 8 additional ET patients (68.1 ± 8.2 years) treated with DBS were assessed in both the ON and OFF state, respectively. The ET related metabolic spatial covariance pattern (ETRP) was characterized by relatively increased metabolism in the cerebellum, brainstem, and temporo-occipital cortices, accompanied by relative metabolic decreases mainly in fronto-temporal and motor cortices. Network expression showed inverse correlations with tremor severity and disease duration and positive correlations with cognitive dysfunction. DBS substantially alleviated tremor, but had only marginal effects on cognitive performance. There were no significant DBS effects on ETRP expression at the group level, but all but one subject showed higher scores in the ON state. Our findings suggest ET is characterized by an abnormal brain network associated with disease phenotype.